2018
DOI: 10.3892/mmr.2018.9721
|View full text |Cite
|
Sign up to set email alerts
|

Pivotal prognostic and diagnostic role of the long non‑coding RNA colon cancer‑associated transcript 1 expression in human cancer (Review)

Abstract: Long non-coding RNAs (lncRNAs) have been classically defined as regulatory RNA members >200 nucleotides in length, without detectable open-reading frames to encode proteins. Previous studies have demonstrated that lncRNAs serve critical roles in multiple cancer types. Colon cancer-associated transcript 1 (CCAT1), a novel cancer-associated lncRNA, is significantly overexpressed in a number of malignancies. Functionally, as an oncogenic lncRNA, CCAT1 is involved in proliferation, migration, cell cycle progressio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 25 publications
(30 citation statements)
references
References 95 publications
1
29
0
Order By: Relevance
“…CCAT1 is a newly discovered oncogenic lncRNA, 2628 bp in length, which is located on chromosome 8q24.21 [46,273]. CCAT1 is firstly found to be upregulated in colon cancer [274] and its expression is suggested to be epigenetically activated by c-Myc [46,275]. There are two isoforms of CCAT1: CCAT1-S and CCAT1-L. CCAT1-S is expressed in the cytoplasm, while CCAT1-L is exclusively expressed in the nucleus.…”
Section: Lncrnas In Colorectal Cancer (Crc)mentioning
confidence: 99%
See 3 more Smart Citations
“…CCAT1 is a newly discovered oncogenic lncRNA, 2628 bp in length, which is located on chromosome 8q24.21 [46,273]. CCAT1 is firstly found to be upregulated in colon cancer [274] and its expression is suggested to be epigenetically activated by c-Myc [46,275]. There are two isoforms of CCAT1: CCAT1-S and CCAT1-L. CCAT1-S is expressed in the cytoplasm, while CCAT1-L is exclusively expressed in the nucleus.…”
Section: Lncrnas In Colorectal Cancer (Crc)mentioning
confidence: 99%
“…There are two isoforms of CCAT1: CCAT1-S and CCAT1-L. CCAT1-S is expressed in the cytoplasm, while CCAT1-L is exclusively expressed in the nucleus. CCAT1-S can be generated from CCAT1-L and there is a positive regulatory relationship between them [275]. CCAT1 is reported to be upregulated in many types of cancer, including CRC, LC, GC, HCC, ESCC, and acute myeloid leukemia (AML) [275,276].…”
Section: Lncrnas In Colorectal Cancer (Crc)mentioning
confidence: 99%
See 2 more Smart Citations
“…6,7 LncRNA colon cancer-associated transcript 1 (CCAT1) plays an important role in the prognosis and diagnosis of human cancers through regulating proliferation, migration, cell cycle progress, chemoresistance and other processes. 8 Moreover, a number of investigators have demonstrated CCAT1 as an oncogene in multiple cancers, such as gastric adenocarcinoma, ovarian cancer, nasopharyngeal carcinoma and lung adenocarcinoma. [9][10][11][12] Notably, Chen et al 13 have reported that CCAT1 contributes to migration and invasion in PCa cells.…”
Section: Introductionmentioning
confidence: 99%